2015
DOI: 10.1007/s10142-015-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of four soybean bZIP genes during Phakopsora pachyrhizi infection

Abstract: Asian soybean rust (ASR), caused by the obligate biotrophic fungus Phakopsora pachyrhizi, is one of most important diseases in the soybean (Glycine max (L.) Merr.) agribusiness. The identification and characterization of genes related to plant defense responses to fungal infection are essential to develop ASR-resistant plants. In this work, we describe four soybean genes, GmbZIP62, GmbZIP105, GmbZIPE1, and GmbZIPE2, which encode transcription factors containing a basic leucine zipper (bZIP) domain from two div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
1
9
1
Order By: Relevance
“…Through VIGS, MebZIP3- and MebZIP5 -silenced plants resulted in disease sensitive, lower transcripts of defense-related genes and less callose depositions. These results are consistent with previous studies that plant bZIP transcription factors are widely involved in plant–pathogen interaction ( Kim and Delaney, 2002 ; Shearer et al, 2012 ; Alves et al, 2013 , 2015 ; Lim et al, 2015 ). Thus, we highlight the positive role of MebZIP3 and MebZIP5 in disease resistance against cassava bacterial blight for further utilization in genetic improvement of cassava resistance to disease.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Through VIGS, MebZIP3- and MebZIP5 -silenced plants resulted in disease sensitive, lower transcripts of defense-related genes and less callose depositions. These results are consistent with previous studies that plant bZIP transcription factors are widely involved in plant–pathogen interaction ( Kim and Delaney, 2002 ; Shearer et al, 2012 ; Alves et al, 2013 , 2015 ; Lim et al, 2015 ). Thus, we highlight the positive role of MebZIP3 and MebZIP5 in disease resistance against cassava bacterial blight for further utilization in genetic improvement of cassava resistance to disease.…”
Section: Discussionsupporting
confidence: 94%
“…Through genome-wide analysis, bZIP gene family has been identified in numerous plant species, including Arabidopsis ( Jakoby et al, 2002 ), pepper ( Capsicum annum ) ( Hwang et al, 2005 ), rice ( Oryza sativa L.) ( Nijhawan et al, 2008 ), maize ( Zea mays L.) ( Wei et al, 2012 ), Populus ( Ji et al, 2013 ), Phaseolus vulgaris ( Astudillo et al, 2013 ), castor bean ( Ricinus communis L.) ( Jin et al, 2014 ), grapevine ( Vitis vinifera ) ( Liu et al, 2014 ), cucumber ( Cucumis sativus ) ( Baloglu et al, 2014 ), Brassica rapa ( Hwang et al, 2014 ), barley ( Hordeum vulgare L.) ( Pourabed et al, 2015 ), Brachypodium distachyon ( Liu and Chu, 2015 ), tomato ( Solanum lycopersicum L.) ( Li et al, 2015 ), legume ( Lablab purpureus L.) ( Wang et al, 2015 ), cassava ( Manihot esculenta ) ( Hu et al, 2016 ), apple ( Malus sieversii L.) ( Zhao et al, 2016 ), and cabbage ( Brassica oleracea ) ( Bai et al, 2016 ). Functional analysis found that plant bZIPs are widely involved in metabolism ( Hartmann et al, 2015 ; Zhang et al, 2015 ; Sagor et al, 2016 ), abiotic stress (salt, drought) ( Inaba et al, 2015 ; Moon et al, 2015 ; Sornaraj et al, 2016 ; Xu et al, 2016 ; Zong et al, 2016 ; Banerjee and Roychoudhury, 2017 ) and plant–pathogen interaction ( Kim and Delaney, 2002 ; Shearer et al, 2012 ; Alves et al, 2013 , 2015 ; Lim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also observed two bZIP TFs up regulated in resistant NIL at 72 and 96 hpi. The bZIPs are the most studied TFs in plants [79] and their role in regulating various metabolic functions such as storage, leaf development, flower development and synthesis of hormones have been investigated [80, 81, 82, 83, 84, 85]. In addition to other functions, bZIP TFs have recently been reported to enhance disease resistance by activating salicylic acid (SA) dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The review by Noman et al [121] described plant bZIP TF responses to different pathogens and summarized the known functions of bZIP TFs as positive or negative regulators of resistance to pathogen infection. A research article by Alves et al [122] described four bZIP genes in soybean ( GmbZIPE1 , GmbZIPE2 , GmbZIP105 , and GmbZIP62 ), and the findings indicated that bZIP proteins contribute to the defense response against Asian soybean rust disease (ASR) through the expression regulation of ASR-related genes. Expression analysis in cassava revealed that MebZIP3 and MebZIP5 were induced by salicylic acid, hydrogen peroxide, and Xanthomonas axonopodis Pv.…”
Section: Bzip Tfsmentioning
confidence: 99%